Analisis Kelembagaan Pada Pengelolaan Sampah Berbasis Masyarakat di Kota Semarang - Prastya, Imam Yudhi; Putri, Nur A. Dwi (Journal of Indonesian Rural and Regional Government, 2025)
Waste management in Semarang City faces complex institutional challenges due to the involvement of multiple actors with differing interests and capacities. This study aims to map the institutional configuration of the waste management system by examining the roles and relationships among formal, semi-formal, and informal actors. A qualitative approach was employed, with data collected through in-depth interviews, field observations, and policy document reviews. The findings reveal that the Environmental Agency (DLH) acts as the main formal actor responsible for coordinating waste management programs, while Waste Banks and TPS 3R (Reduce, Reuse, Recycle) operate as semi-formal institutions-legally recognized by government regulations but managed voluntarily and participatory by local communities. Meanwhile, informal actors, such as household waste collectors, itinerant buyers, and waste pickers, contribute to the circulation of recyclable materials despite being outside formal regulation. Limited coordination and differing interests among actors hinder optimal collaboration. This study emphasizes that institutional mapping serves as an initial step toward understanding the dynamics of community-based waste management. Further research is recommended to apply Ostrom’s Institutional Analysis and Development (IAD) framework to analyze interactions among rules, actors, and outcomes in greater depth.